Patients experiences with multiple sclerosis disease-modifying therapies in daily life - a qualitative interview study - Anna Sippel; Karin Riemann-Lorenz; Jutta Scheiderbauer; Ingo Kleiter; Rebecca Morrison; Christopher Kofahl; Christoph Heesen (BMC, 2021)
Abstract Background Besides coping with a disease with many uncertainties, people with relapsing-remitting multiple sclerosis face complex decisions concerning disease-modifying therapies (DMTs). In an interview study, we aimed to assess patients' experiences with DMTs. Methods Problem-centred interviews were conducted with 50 people with relapsing-remitting multiple sclerosis in Germany using maximum variation sampling and covering all licensed DMTs. Data were analysed thematically using deductive and inductive categories. Results 47 of 50 patients had treatment with at least one of the approved DMTs. The main themes were: (1) starting a DMT, (2) switching to another DMT, (3) discontinuing a DMT, and (4) multiple sclerosis without starting a DMT. Different intercorrelated factors influenced the decision-making processes for or against a DMT. Individual experiences with DMTs in daily life contained the effort in administration, success, and failure of DMTs, coping strategies and well-being without DMTs. The decision-making process for or against a DMT and the use of those treatments can be understood as a constant, continually shifting process, complicated by different factors, which change over time. Experiences with DMTs were characterized by attempts to handle uncertainty and to (re)gain control and integrate adaptivity into one's life. Conclusions The study provides a rich and nuanced amount of patients' experiences with DMTs. The findings demonstrate the importance for practitioners to look at current life circumstances of patients with multiple sclerosis when recommending a DMT and to promote and enable patients to make informed decisions.